2006
DOI: 10.1002/macp.200600389
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Hybrid Nanocomposites Coated on LDPE

Abstract: Summary: Hybrid organic‐inorganic nanocomposites containing hyperbranched structures were prepared through a dual‐curing process, which involves photopolymerization and condensation alkoxysilane groups. In particular, an oligomer containing PEO units and α,ω‐methacrylate groups was used together with a HBP bearing acrylic groups as the organic phase precursors. MEMO, as the organic‐inorganic linker, and TEOS, as inorganic phase precursor, were also employed. The kinetics of both photopolymerization and condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Owing to its pending methyl group close to carbonyl, PLLA interacts with titanium to a lower degree, thus maintaining its crystallizing ability in the hybrid, whereas crystallization of PCL and PBG is prevented by the strong interaction between these polymers and the inorganic phase. A similar behavior has been previously reported not only for PBG-containing hybrids (38) but also for silica-based hybrids containing a crystallizable polymer (44)(45)(46)(47), where crystallization of the polymeric component was found to be strongly reduced or even totally inhibited owing to organic-inorganic phase interaction.…”
Section: Resultssupporting
confidence: 87%
“…Owing to its pending methyl group close to carbonyl, PLLA interacts with titanium to a lower degree, thus maintaining its crystallizing ability in the hybrid, whereas crystallization of PCL and PBG is prevented by the strong interaction between these polymers and the inorganic phase. A similar behavior has been previously reported not only for PBG-containing hybrids (38) but also for silica-based hybrids containing a crystallizable polymer (44)(45)(46)(47), where crystallization of the polymeric component was found to be strongly reduced or even totally inhibited owing to organic-inorganic phase interaction.…”
Section: Resultssupporting
confidence: 87%
“…The use of a coupling agent can also be exploited to create chemical bonds between the two phases. 18 The aim of this work is to use the dual-curing process in the case of water-based resins and to prepare UV-cured nanocomposite coatings based on a waterborne polyurethane acrylic resin and containing nanosilica prepared in situ by sol-gel. The article presents a morphological investigation of the nanocomposites which allowed the determination of the best preparation conditions and chemical composition of the UV-curable mixture.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Hyb‐75, for which the highest number of TiOC covalent bonds was revealed by FT‐IR measurements (Figure 3), the interaction between the phases is so strong that almost no glass transition is detected, despite the fact that in this hybrid the amount of polymer is more than 50 wt.‐%. For Class II hybrids it was previously reported that the glass transition temperature of polymers whose chain ends are locked into the inorganic network increases upon hybrid synthesis 60–63. However the T g values reported in Table 3 show an opposite trend, with the T g in the hybrid samples being lower than in the PTMC polymer precursor.…”
Section: Resultsmentioning
confidence: 83%